Increasing Income Through The Karwo Cake Center In Tanggilingo Village, Kabila Sub-District, Bone Bolango District - Sin Boki (Penerbit Jurnal Indonesia, 2024)
The aim of this research is to determine the increase in income through the Karawo Cake Center IKM in Tanggilingo Village, Kabila District, Bone Bolango Regency. This research method uses a descriptive type of research with a qualitative approach. Data collection techniques were carried out through observation and interviews using interview guidelines which were given to a number of informants. Based on the research results, based on several interviews with research informants above, it can be concluded that the human resource improvement program has been running well by involving employees in various training held by agencies such as raw material agents. Even though they have participated in the training, there are still some employees who have not been able to develop their skills because the training was held when they were invited by the relevant agencies. But that doesn't hinder business management at IKM Sentra Karawo. Based on the results of interviews with several informants above, it can be concluded that the current facilities are adequate and are no longer an obstacle to managing the Karawo Cake Center IKM business anymore because the owner and employees work together to optimize deficiencies by collecting personal money to buy the facilities so as not to experience losses. Based on the results of interviews with several informants above, it can be concluded that the role of capital is very important for SMEs. The capital owned by IKM Sentra Karawo is sufficient to meet production needs and does not become an obstacle to managing the IKM Cake Karawo Center business in increasing community income in Tanggilingo Village, Kabila District, Bone Bolango Regency.